Prevalência de infecção latente pelo Mycobacterium tuberculosis entre profissionais de saúde da atenção básica no município de Vitória, ES - Lacerda, Thamy Carvalho (2013)
Despite being one of the most important causes of morbidity and mortality worldwide, TB remains a neglected problem in developing countries and a major grievance in Public Health, evidenced by its transcendence, magnitude and vulnerability. Furthermore, coinfection with human immunodeficiency virus (HIV) and the emergence of resistant strains are configured in new barriers and important challenges facing the world. Among those at risk of infection, health professionals are the most vulnerable, as already shown in some publications. In 2004, the Brazilian Ministry of Health emphasized the integration of the activities of the National TB Control for all services of the Unified Health System following its guidelines of "flattening" and decentralization in the fight against TB. This is a cross-sectional study in which data were collected through a questionnaire assessing sociodemografh and occupational characteristics, information about tuberculosis and exposure. This was followed by the application of the tuberculin skin test, evaluated after 72 hours by skilled professional, and its result based on cutoffs point positive in 10mm e 5mm induration. Participants in the study included 226 volunteers and resulted in a loss of 2,1%. We obtained a prevalence of positive test 40,7% and 54,9% for both cutoffs. The association between the time of exercise ≥ 5 years and the TST for cutoff of 5 mm was statistically significant (p = 0). Despite the downward trend in the number of new cases, it is concluded that the Health Care Workers at a Primary Health Care Clinic are exposure to this disease. Given the indifference of Public Entity and hence the impact of the biosecurity, there need to be strengthened politically effective actions impacts on Occupational Health of Primary facing these professionals.